Improving hydropower generation scheduling and dispatching decisions with Python simulator - Stoenescu, Ionut Bogdan; Costinas, Sorina (Scientific Bulletin. Series C, Electrical Engineering and Computer Science, 2025)
Variable renewable energy sources and recent developments in energy markets cause problems for hydropower plants real-time operation and unit commitment. The 15 minutes settlement period force the renewable energy asset owners to trade more frequently to balance their position, otherwise the imbalances can be very costly. In the last year, we can observe increased transaction volumes in European intraday power market (SIDC) compared to previous years. Such transactions and balancing market orders modify the generation schedules of hydropower units and increase the need for fast estimation of the lakes levels, spillage and infeasible generation units schedule. This estimation can be achieved in seconds with the generation schedules simulator proposed in this paper and implemented in Python. The simulator was tested on real data from 5 hydropower plants. The results confirm the accuracy of the algorithm and provides insights into the modelling of input data. The article focus on presenting the details of hydropower generation schedules simulation algorithm, implementation of it in Python and testing on real data from 5 hydropower plants. The practical implementation of the algorithm allow the dispatcher to adjust the schedules of generating units and predict if they are unfeasible or spillage will occur, based on simulated levels.